Preparation of size controllable polymer fluorescent microspheres by self-stabilized precipitation polymerization. (15th October 2022) - Chen, Weiqing; Zhang, Jianping; Zhao, Yun; Wang, Zhengge; Wu, Zhaoji; Wu, Nannan; Wang, Rujing; Zhang, Zhigang
ABSTRACT: In contrast to small fluorescent molecules, fluorescent microspheres are easier to be modified and more stable. In this work, a novel fluorescent microsphere was obtained by ternary copolymerisation of maleic anhydride (MAn), vinyl acetate (VAc) and fluorescent monomer containing Rhodamine B group (FM-Rh B). The morphology, structure, composition and fluorescent performances of the fluorescent microspheres were characterised by scanning electron microscope, Fourier transform infrared spectrometer, UV–vis spectrophotometer, and fluorescence spectroscope. The results show that the surface of the fluorescent microspheres was smooth and free of impurities, which are conducive to its application in the fields of biology and medicine. The microspheres display good fluorescence properties under both blue and green light, which expands the application of these microspheres. It can emit strong fluorescence at 566 nm even in polar solvents. The size of the fluorescent microspheres is in the range of 184–1022 nm and can be controlled by changing polymerisation conditions.